Desarrollo de una bomba para la evaluación de bioprótesis valvulares cardiacas - González Téllez, Víctor Alfonso (My University, 2014)
Desarrollo de una bomba para la evaluación de bioprótesis valvulares cardiacas
Desarrollo de una bomba para la evaluación de bioprótesis valvulares cardiacas
Keywords: Desarrollo de una bomba para la evaluación de bioprótesis valvulares cardiacas